Highly dispersive optical soliton perturbation with cubic-quintic-septic law via two methods - Ali, Khalid K.; Rezazadeh, Hadi; Raza, Nauman; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2021)
The main consideration of this paper is to discuss cubic optical solitons in a polarization-preserving fiber modeled by nonlinear Schrodinger equation (NLSE). We extract the solutions in the forms of hyperbolic, trigonometric including a class of solitary wave solutions like dark, bright-dark, singular, singular periodic, multiple-optical soliton and mixed complex soliton solutions. A recently developed integration tool known as new extended direct algebraic method (NEDAM) is applied to analyze the governing model. Moreover, the studied equation is discussed with two types of nonlinearity. The constraint conditions are explicitly presented for the resulting solutions. The accomplished results show that the applied computational system is direct, productive, reliable and can be carried out in more complicated phenomena.
Keywords: Optical solitons; NEDAM; refractive index; integrability